Pengaruh Penggunaan Rumput Kebar (Biophytum petsianum Clotzch) dalam Konsentrat Berdasarkan Kandungan Protein Kasar 19% terhadap Penampilan Kelinci - Kayadoe, Martha; Faidiban, O R; Purwaningsih, Purwaningsih; Nurhidayati, Dwi (Universitas Sebelas Maret (UNS), 2012)
The objective of this study was to investigate the performances of rabbit using several levels of Kebar grass in concentrate, i.e. 0, 5, 10 and 15%, according to protein requirement 19%. Research designed by using Randomized Design Group and each treatment was replicated two times. Data were analyzed using Analysis of Variance and Continued with LSD test. The addition of kebar grass concentrates had no effect in ration and feed efficiency, but significantly affect body weight gain in treatment of 10% and 15% compared to without addition (0%) of kebar grass and 5%. The addition of kebar grass did not affect palatability.Key words : kebar grass, rabbit, concentrate, formulations